Recombinant Peptide Production Platform Coupled with Site-Specific Albumin Conjugation Enables a Convenient Production of Long-Acting Therapeutic Peptide - Mijeong Bak; Junyong Park; Kiyoon Min; Jinhwan Cho; Jihyoun Seong; Young S. Hahn; Giyoong Tae; Inchan Kwon (MDPI AG, 2020)
The number of therapeutic peptides for human treatment is growing rapidly. However, their development faces two major issues: the poor yield of large peptides from conventional solid-phase synthesis, and the intrinsically short serum half-life of peptides. To address these issues, we investigated a platform for the production of a recombinant therapeutic peptide with an extended serum half-life involving the site-specific conjugation of human serum albumin (HSA). HSA has an exceptionally long serum half-life and can be used to extend the serum half-lives of therapeutic proteins and peptides. We used glucagon-like-peptide 1 (GLP-1) as a model peptide in the present study. A "clickable" non-natural amino acid-p-azido-l-phenylalanine (AzF)-was incorporated into three specific sites (V16, Y19, and F28) of a GLP-1 variant, followed by conjugation with HSA through strain-promoted azide-alkyne cycloaddition. All three HSA-conjugated GLP-1 variants (GLP1_16HSA, GLP1_19HSA, and GLP1_28HSA) exhibited comparable serum half-lives in vivo. However, the three GLP1_HSA variants had different in vitro biological activities and in vivo glucose-lowering effects, demonstrating the importance of site-specific HSA conjugation. The platform described herein could be used to develop other therapeutic peptides with extended serum half-lives.